The Method Habib Musthafa Al-Jufri in Teaching Reading The Book of Tafsir Al Jalalain - Nur Kholifa; Agus Nu'man (STAI Nurul Huda Kapongan Situbondo, 2022)
This research is motivated by the advantages of Habib Mustafa Al-Jafri's method in teaching the book of Tafsir Jalaleen, and specifically in the method of learning his book, which is very different from others. This research uses the qualitative descriptive method with the design of a field research study. In this study, researchers used observational, interview, and documentation methods as a means of collecting data from primary and secondary data sources. The results of this study: (1) The inheritance book, which was studied according to the books of past and current scholars. (2) The method of learning the inheritance book at the Islamic Institute is the Surugan method. (3) Factors supporting learning the book Al-Tawrat at the Islamic Institute Noor Al-Huda is a professor, all of them can read the book Al-Tawrat. While the disincentive is that some students have not mastered grammar/conjugation or instrumental science.